Enhancement of biogas production process from biomass wastes using iron-based additives: types, impacts, and implications. Issue 2 (15th June 2022) - Ugwu, Samson Nnaemeka; Enweremadu, Christopher Chintua
ABSTRACT: In this study, the impacts of various iron-based additives on anaerobic digestion of biomass and the fate of the iron-rich digestates on the ecosystem were reviewed. Anaerobic digestion of biomass is a green energy technology with known environmental benefits for biogas production. However, increasing interest in this technology has triggered the need to improve biogas yield from existing substrates and to enhance the biodegradability of biomasses of lignocellulosic (≥70%), complex molecular nature, and novel substrates, necessitating the use of several enhancement techniques. Among the enhancement options, the influence of iron-based additives on methanogens as it relates to their electron donation/acceptor capabilities and as a cofactor of key enzymatic activities have been highlighted as being outstanding in enhancing anaerobic digestion processes. The reviewed iron-based additives classified based on their forms were either synthesized or naturally occurred as liquids, nanoparticles, solids or powders and applied to bio-digestion processes at different dosages. These reviewed iron-based additives were reported to have influenced biogas yields and methane contents, solids and volatile fatty acids, reduction of antibiotic-resistant genes (ARGs), pathogens, and pharmaceutical and personal care products (PPCPs), etc. Aside these proven benefits, the environmental implications of non-degradability of iron complexes formed during iron supplemented anaerobic digestion and their fate after digestates disposal calls for concern. However, this study recommends that research on the use of cross-linkers, extra-polymeric substances and antagonists alongside iron-based additives could play a vital role in preventing up to 90% iron complexes formation while enhancing biogas yields.